2016
DOI: 10.1016/j.ijsu.2016.07.050
|View full text |Cite
|
Sign up to set email alerts
|

Surgical techniques for osteoporotic vertebral collapse with delayed neurological deficits: A systematic review

Abstract: Although the optimal treatment has not been determined for patients of OVC with DND in this study, our analysis could provide guidance for choosing an appropriate approach. Besides, effective treatment for OVC with DND requires multidisciplinary collaboration, such as geriatricians, interventional radiologists, respiratory disease experts, and spine surgeons. On light of the above analysis, we believe that individualized surgical approach should be introduced based on the clinical characteristics of each patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…In this study, we evaluated the surgical outcomes for OVF in the lower lumbar spine with neurological deficits. Previous reports revealed that OVF with neurological deficits frequently develop at the thoracolumbar junction area and that there are few patients with OVF in the low lumbar spine 6,11,15,16 . As a result, the surgical outcomes of lumbar OVF were still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we evaluated the surgical outcomes for OVF in the lower lumbar spine with neurological deficits. Previous reports revealed that OVF with neurological deficits frequently develop at the thoracolumbar junction area and that there are few patients with OVF in the low lumbar spine 6,11,15,16 . As a result, the surgical outcomes of lumbar OVF were still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies are case series at a single or small group of institutions, and studies with large sample sizes are scarce. There is one previous large-scale systematic review of 29 papers that included 596 OVF patients with delayed neurological deficits 16 . However, the majority of patients (93.8%) in that review had OVF at the thoracolumbar region (T10-L2).…”
Section: Introductionmentioning
confidence: 99%
“…Vertebral body collapse, kyphosis, persistent back pain, or disability might occur after vertebral fractures if not treated adequately. 18 , 19 Though the management of thoracolumbar fracture remains a matter of discussion, 20 many surgeons advocate surgical treatment, especially for unstable fractures or neurologically compromised patients. 18 , 19 , 21 Surgical procedures have included decompression, anterior or posterior fixation, or both, with or without fusion.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies from other countries such as China, France or Korea; however, the number of patients in their samples were small and studies with a large number of patients is limited [15][16][17] . There is one previous, large-scale, systematic review that included 596 OVF patients with delayed neurological deficit from 29 publications 9) . In this review, posterior surgery was conducted in 60.6% of patients followed by anterior decompression and reconstruction in 36.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these studies are case series at a single institution, or cohort studies from a few institutions; studies with a large sample size are limited. There is one systematic review that included 596 patients from 29 publications comparing three different surgical methods: anterior decompression and reconstruction, posterior surgery, and posteroanterior surgery 9) . However, inclusion criteria may vary among the studies, so it is difficult to perform statistical analysis comparing each surgical pro-cedure, or on various radiological parameters, as the data from each individual patient was not available in this systematic review.…”
Section: Introductionmentioning
confidence: 99%